GAMBARAN KEPATUHAN DIET DAN KONTROL GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 SETELAH KONSELING GIZI DI PUSKESMAS AIR DINGIN TAHUN 2022 - Sepni Asmira; Fauzan Azima; Kesuma Sayuti; Armenia Armenia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion and insulin resistance. The 2018 health profile survey showed that the highest prevalence of type 2 DM was in the working area of the Air Dingin Health Center, including high compared to other puskesmas in the Koto Tangah sub-district with 442 cases of DM. The aim of the study was to find out the description of dietary compliance and blood sugar control in type 2 DM patients at the Air Cold Health Center after nutritional counseling in 2022. This type of quasi-experimental research used the One Group Pretest Posttest design. Samples were taken using total sampling. The total sample was 37 people who met the inclusion and exclusion criteria. Data on blood sugar levels were measured using a glucometer. The data normality test used the Shapiro-Wilk test and the analysis used the Wilocoxon test. The results showed that there was a decrease in the average blood glucose level. There is a significant effect on blood sugar levels, there is no significant effect on adherence in terms of the amount of food on total energy and carbohydrates and there is a significant effect on adherence to protein and fat, there is a significant effect on adherence in terms of the type of food and there is a significant effect on adherence in terms of schedule Meals before and after nutritional counseling.